Are Transient Institutions Sophisticated Enough to Interpret Small Negative Earnings Surprises?. (January 2018) - Trabelsi, Samir
Institutional investors (active vs. passive) play various roles in the capital market and in assets prices, in particular. Institutional investors affect assets prices either because they play a monitoring role and mitigate the agency problem, or because they have information advantages, or finally, they can arbitrage away mispricing. This research note relates Hu, Ke, and Yu's (forthcoming) article to both the traditional positive views that institutional investors are sophisticated and help correct stock mispricing and the complementary emerging literature that argues that institutions may contribute to stock return anomalies rather than eliminate them. My research note concludes that current research on the role of institutional investors has generated a number of useful insights. I identify many fundamental questions that remain unanswered, and changes in the economic environment that raise new questions for research.